(untitled) - Beveridge, Malcolm C. M (Oxford, UK, 2004)
This is the third edition of a book first published seven years ago. The book and cage aquaculture have come a long way in that time.
Keywords: Cage aquaculture,Cage aquaculture,Bể nuôi trồng thuỷ sản,Bể nuôi trồng thuỷ sản; Environmental aspects,Khía cạnh môi trường